Effects of dextromethorphan as add‐on to sitagliptin on blood glucose and serum insulin concentrations in individuals with type 2 diabetes mellitus: a randomized, placebo‐controlled, double‐blinded, multiple crossover, single‐dose clinical trial. Issue 1 (26th October 2015) - Marquard, J.; Stirban, A.; Schliess, F.; Sievers, F.; Welters, A.; Otter, S.; Fischer, A.; Wnendt, S.; Meissner, T.; Heise, T.; Lammert, E.
Abstract : In this clinical trial, we investigated the blood glucose (BG)‐lowering effects of 30, 60 and 90 mg dextromethorphan (DXM) as well as 100 mg sitagliptin alone versus combinations of DXM and sitagliptin during an oral glucose tolerance test (OGTT) in 20 men with T2DM. The combination of 60 mg DXM plus 100 mg sitagliptin was observed to have the strongest effect in the OGTT. It lowered maximum BG concentrations and increased the baseline‐adjusted area under the curve for serum insulin concentrations in the first 30 min of the OGTT (mean ± standard deviation 240 ± 47 mg/dl and 8.1 ± 6.1 mU/l/h, respectively) to a significantly larger extent than did 100 mg sitagliptin alone (254 ± 50 mg/dl and 5.8 ± 2.5 mU/l/h, respectively; p < 0.05) and placebo (272 ± 49 mg/dl and 3.9 ± 3.0 mU/l/h, respectively; p < 0.001). All study drugs were well tolerated, alone and in combination, without serious adverse events or hypoglycaemia. Long‐term clinical trials are now warranted to investigate the potential of the combination of 30 or 60 mg DXM and dipeptidyl peptidase‐4 inhibitors in the treatment of individuals with T2DM, in particular as preclinical studies have identified the β‐cell protective properties of DXM.